Identification for Development : Liberia - World Bank (World Bank, Washington, DC, 2017)
The Government of Liberia (GOL) enacted the national identification registry (NIR) act in 2011 to establish national identification in the country. The law called for the setup of a NIR to be responsible for issuing a biometric-based identification card to each citizen and resident in Liberia. The development of digital identity in Liberia can help the country’s economic and social development. This report provides a rapid study of the potential and readiness of digital identity in Liberia. The report is based on consultations held with the GOL and stakeholders in Liberia during 2014 and 2015. The report provides a preliminary review of the enabling environment and the functional identity programs in Liberia, and discusses next steps. Further assessment of the enabling environment and a detailed action plan will be needed for the GOL to pursue developing digital identity in the country.